Clinical characteristics, outcomes, and predictors of leptospirosis in patients admitted to the medical intensive care unit: A retrospective analysis. Issue 12 (December 2020) - Ajjimarungsi, Atta; Bhurayanontachai, Rungsun; Chusri, Sarunyou
Abstract: Background: Early diagnosis and detection of clinical deterioration of leptospirosis are challenges to all clinicians. This study aimed to report the characteristics and outcomes of patients admitted to the medical intensive care unit (MICU) for severe leptospirosis and to identify the clinical predictors of MICU admission. Methods: This was a 10-year retrospective study that included all patients diagnosed as leptospirosis, based on either serology or a Thai-Lepto score (TLS) of >4. All clinical characteristics and laboratory data were collected and compared between MICU cases and general ward cases. Binary logistic regression was applied to identify the independent factors for MICU admission. Results: Of the 68 patients who were diagnosed as leptospirosis based on inclusion criteria, 43 serologically-confirmed cases were subsequently analyzed. Fifty percent of the cases were admitted to the MICU and, compared with those admitted to the general ward, had higher Sequential Organ Failure Assessment (SOFA) score [10 (7–13) vs. 5 (2.2–5.6), p < 0.001]; higher TLS [7.5 (6.5−9.25) vs. 5.5 (3.5−6.5), p < 0.001]; lower mean arterial blood pressure (74.7 ± 15 mmHg vs. 84.2 ± 16.3 mmHg, p = 0.04); lower platelet count in ×10 3 cell/mm 3 [65 (52.8–105.8) vs. 159 (87.3–181.5), p = 0.008); higher total bilirubin level [4.4 (1.5–8.7) mg/dL vs. 1.2 (0.7–2.8) mg/dL, p = 0.01]; and required more inotropes and vasopressors (87% vs. 4.3%, p < 0.001), mechanical ventilator support (91.3% vs. 4.3%, p < 0.001), and renal replacement therapy (39.1% vs. 0%, p < 0.001). TLS, SOFA score, requirement for mechanical ventilation, and use of inotropes and vasopressors were the predictors of MICU admission. TLS > 6 and SOFA score >6 gave similar power to predict MICU admission. Conclusion: Among patients with leptospirosis, TLS, SOFA score, inotrope or vasopressor requirement, and mechanical ventilator support were the independent predictors of MICU admission. TLS > 6 and SOFA score >6 indicated the need for MICU admission.